"Enotnost v različnosti" - Banjac, Marinko (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2011)
Multiculturalism in the European Union defines the framework for the regulation of cultural diversity, and in this the idea of "unity in diversity" is one of the key elements, since it provides a rationale for the process of constructing the European Union. The paper aims to show that multiculturalism is a specific governmental technology that opens up political space and allows the expression of diversity by different collective subjectivities. But this formation of the freedom of collective subjectivities is a kind of control within modern governmental mechanisms, and provides the conditions for potential new exclusions. European populations are determined by identifying those groups and individuals that are "dangerous" to the inhabitants of Europe, while European multicultural individuals are perceived to be tolerant and flexible. Since the European space is predominantly understood as an open economy, individuals in this space are constructed as a mobile and capable workforce ready to adapt to changes in a global economy.
Keywords: Multiculturalism; Multikulturalizem; Cultural policy; Kulturna politika; Neoliberalism; Neoliberalizem; Europe; Evropa; večkulturnost